Studies toward the comprehension of fungal-macroalgae interaction in cold marine regions from a biotechnological perspective - Martorell, M.M. (2021)
In marine ecosystems, macroalgae are the habitat for several microorganisms, fungi being among them. In the Antarctic benthic coastal ecosystem, macroalgae play a key role in organic matter cycling. In this study, 13 different macroalgae from Potter Cove and surrounding areas were sampled and 48 fungal isolates were obtained from six species, four Rhodophyta Ballia callitricha, Gigartina skottsbergii, Neuroglossum delesseriae and Palmaria decipiens, and two Phaeophyceae: Adenocystis utricularis and Ascoseira mirabilis. Fungal isolates mostly belonged to the Ascomycota phylum (Antarctomyces, Cadophora, Cladosporium, Penicillium, Phialocephala, and Pseudogymnoascus) and only one to the phylum Mucoromycota. Two of the isolates could not be identified to genus level, implying that Antarctica is a source of probable novel fungal taxa with enormous bioprospecting and biotechnological potential. 73% of the fungal isolates were moderate eurypsychrophilic (they grew at 5–25 °C), 12.5% were eurypsychrophilic and grew in the whole range, 12.5% of the isolates were narrow eurypsychrophilic (growth at 15–25 °C), and Mucoromycota AUe4 was classified as stenopsychrophilic as it grew at 5–15 °C. Organic extracts of seven macroalgae from which no fungal growth was obtained (three red algae Georgiella confluens, Gymnogongrus turquetii, Plocamium cartlagineum, and four brown algae Desmarestia anceps, D. Antarctica, Desmarestia menziesii, Himantothallus grandifolius) were tested against representative fungi of the genera isolated in this work. All extracts presented fungal inhibition, those from Plocamium cartilagineum and G. turquetii showed the best results, and for most of these macroalgae, this represents the first report of antifungal activity and constitute a promising source of compounds for future evaluation.